Q. 5 F4.3( 6 Votes )

Let U = {1, 2, 3,

B – C is defined as {x ϵ B : x C}

B = {2, 4, 6, 8}

C = {3, 4, 5, 6}

B – C = {2, 8}

Now, (B – C)’ = U – (B – C)

U = {1, 2, 3, 4, 5, 6, 7, 8, 9}

B – C = {2, 8}

(B – C)’ = {1, 3, 4, 5, 6, 7, 9}.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Let A = {a, b, c,RS Aggarwal - Mathematics

If A and B be twoRS Aggarwal - Mathematics

(i) If A <span laRS Aggarwal - Mathematics

Using propeMathematics - Exemplar

If A and B are twRS Aggarwal - Mathematics

In a town of 10,0RS Aggarwal - Mathematics

If A and B are twRS Aggarwal - Mathematics

If <a name="MTBlaRS Aggarwal - Mathematics

If n(A) = 3 and nRS Aggarwal - Mathematics

For any sets A, BRS Aggarwal - Mathematics